NAVIGATING UNCERTAINTY: PALM OIL SECTOR OUTLOOK FOR 2026 THROUGH THE LENS OF SMALLHOLDER WELFARE AND SUSTAINABILITY IMPERATIVES - Judijanto, Loso (Seven Editora, 2026)
This qualitative literature review examines the outlook for Indonesia's palm oil sector in 2026, with particular emphasis on smallholder farmers' welfare and the interplay between production dynamics, policy drivers, and sustainability imperatives. Synthesizing evidence from the 2026 IPOSS Palm Oil Outlook, literature publications (2020-2025), and government reports. In industry analyses, we identify critical determinants shaping the sector's trajectory: biodiesel mandate expansion (B40-B50), climate variability following El Niño-La Niña cycles, implementation of the European Union Deforestation Regulation (EUDR), and persistent productivity gaps in smallholder plantations. Global crude palm oil (CPO) production is projected at 83 million metric tons in 2026, with Indonesia maintaining 59% market share despite land expansion constraints and bottlenecks in the replanting program (PSR). Domestic consumption intensification through bioenergy mandates creates a dual pressure on export capacity and farmer income stability. Price forecasts range from USD 1,050 to 1,200/MT, influenced by energy policy, geopolitical tensions, and sustainability compliance costs. Thematic findings reveal that smallholder welfare—measured through Farmers Terms of Trade (NTP) and multidimensional welfare indices—remains vulnerable to price volatility, limited market access, and certification barriers. We propose six evidence-based policy recommendations prioritizing accelerated replanting (200,000 ha/year target), price stabilization mechanisms, subsidized ISPO certification pathways, enhanced extension services, comprehensive welfare monitoring systems, and income diversification strategies. This review contributes to agricultural economics literature by synthesizing fragmented research streams and providing actionable insights for policymakers navigating the sustainability-development nexus in commodity-dependent economies.DOI: https://doi.org/10.56238/sevened2026.008-062